2021
DOI: 10.3389/fonc.2021.647598
|View full text |Cite
|
Sign up to set email alerts
|

Profiling Oncogenic Germline Mutations in Unselected Chinese Lung Cancer Patients

Abstract: IntroductionEmerging evidence has suggested that inherited factors are also involved in lung cancer development. However, most studies focused on well-elucidated cancer predisposition genes, the majority of which are tumor suppressor genes. The profile of germline mutations in oncogenic driver genes remains unrevealed, which might also provide potential clinical implications for lung cancer management.MethodsSequencing data from 36,813 unselected lung cancer patients who underwent somatic mutation profiling we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 31 publications
0
7
1
Order By: Relevance
“…In the current study, we identified a MUTYH germline mutation in one ovarian cancer patient. A previous study in 36,813 Chinese lung cancer patients, focusing on eight key lung cancer driver genes (EGFR, ALK, MET, KRAS, ERBB2, ROS1, RET, and BRAF), revealed a prevalence of 0.03% for P/LP germline mutations [30]. However, we did not find germline mutations in these genes.…”
Section: Discussioncontrasting
confidence: 85%
“…In the current study, we identified a MUTYH germline mutation in one ovarian cancer patient. A previous study in 36,813 Chinese lung cancer patients, focusing on eight key lung cancer driver genes (EGFR, ALK, MET, KRAS, ERBB2, ROS1, RET, and BRAF), revealed a prevalence of 0.03% for P/LP germline mutations [30]. However, we did not find germline mutations in these genes.…”
Section: Discussioncontrasting
confidence: 85%
“…For instance, with the advent of next generation sequencing (NGS), many large-scale surveys of known and suspected germline mutations in cancer patients have now been conducted. These surveys have provided even more exacting estimates of the true prevalence of heritable cancers [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39]. Additionally, dozens of large-scale genome-wide association studies (GWAS) for many cancers have also been pursued.…”
Section: The Genetics Of Familial Cancermentioning
confidence: 99%
“…These 12 types of cancer account for ~78% of all known cancer cases in the US [55], and therefore, the numbers generated from this analysis can be reasonably extrapolated to all cancer types. [20] 11.0 [41] 57 [18] Lung 235,760 [55] 0.3-1.4 [27][28][29] Ave. = 0.9 8.7 [20] 0.7 [42] 18 [18] Colorectal 149,500 [55] 3.5-7.5 [30,31] Ave. = 5.5 12.8 [20] 1.2 [43] 15 [18] Melanoma 106,110 [55] 1.9-3.1 [32,33] Ave. = 2.5 4.9 [20] 0.9 [44] 58 [18] Bladder 83,730 [55] 8.9 [34] 5.4 [20] 0.9 [45] 30 [18 1. First, the prevalence of heritable cancers derived from NGS analysis of high penetrance germline mutations (Table 1, Column 3, Germline Prevalence) varies much more than the traditional "5-10%" that is often quoted [16,17], indeed, it ranges from a low of 0.3% in lung cancer to a high of 17.2% in prostate cancer.…”
Section: The Genetics Of Familial Cancermentioning
confidence: 99%
“…For instance, germline mutations in BRAC2 were found to be associated with a higher risk and early onset of lung cancer in Chinese population [ 19 , 20 ]; however, such an association was not observed in several studies with European ancestry as study subjects [ 2 ], emphasizing the need to characterize the landscape of ethnicity‐specific harmful inherited genetic variations. Some studies have been conducted to pinpoint genes and loci associated with susceptibility to lung cancer in Chinese population [ 9 , 20 , 21 , 22 , 23 , 24 ]. Existing studies have some limitations such as small sample size, few covered genes, and lack of somatic mutation data, reducing the ability of finding rare germline variants and the exploration of the interaction between germline and somatic mutations.…”
Section: Introductionmentioning
confidence: 99%